Exploring the ferromagnetic behaviour of a repulsive fermi gas via spin dynamics - Valtolina, Giacomo; Enss, Tilman (Arxiv, 2017)
Ferromagnetism is a manifestation of strong repulsive interactions between itinerant fermions in condensed matter. Whether short-ranged repulsion alone is sufficient to stabilize ferromagnetic correlations in the absence of other effects, like peculiar band dispersions or orbital couplings, is however unclear. Here, we investigate ferromagnetism in the minimal framework of an ultracold Fermi gas with short-range repulsive interactions tuned via a Feshbach resonance. While fermion pairing characterises the ground state, our experiments provide signatures suggestive of a metastable Stoner-like ferromagnetic phase supported by strong repulsion in excited scattering states. We probe the collective spin response of a two-spin mixture engineered in a magnetic domain-wall-like configuration, and reveal a substantial increase of spin susceptibility while approaching a critical repulsion strength. Beyond this value, we observe the emergence of a time-window of domain immiscibility, indicating the metastability of the initial ferromagnetic state. Our findings establish an important connection between dynamical and equilibrium properties of strongly-correlated Fermi gases, pointing to the existence of a ferromagnetic instability.
Gesehen am 23.11.2017